First approach to studying the genetics of the meagre (Argyrosomus regius; Asso, 1801) using three multigene families. Issue 6 (21st February 2012) - Merlo, Manuel Alejandro; Cross, Ismael; Rodríguez‐Rúa, Ana; Manchado, Manuel; Rebordinos, Laureana
Abstract The meagre (Argyrosomus regius) is a commercially important species for fisheries, and aquaculture production has been increasing in recent years. However, this growing importance has not been matched by increased genetic knowledge of the species. For this reason, an initial approach has been made to understanding the genetics of the meagre, using three particular multigene families (45S and 5S ribosomal DNA and U2 snRNA gene) as both molecular and cytogenetic markers. Only one type of 5S rDNA and only one ITS‐1 (from 45S rDNA) were obtained, and these therefore could provide the basis for the development of genetic markers for this species. However, the U2 snRNA gene produced a multi‐band electrophoretic pattern, and some of these bands were demonstrated to be linked with the U1 snRNA gene. This linkage could also provide a good species‐specific marker which could be useful for tracing the evolutionary history of the Sciaenidae family. In this study, we have described for the first time the karyotype of the meagre: this is composed of 48 acrocentric chromosomes. Each of the three gene families were localized on different chromosome pairs, although the U2 snRNA gene probe was also located scattered throughout the genome of the meagre, as expected by the amplification pattern.